Evaluation of the detuning ratio as a tool to detect potential interference in LC-MSMS analysis - Arber Rexhaj; Michael Vogeser; Katharina Habler (Journal of Mass Spectrometry and Advances in the Clinical Lab, 2025)
Objective: Tandem mass spectrometry (MS/MS) is highly specific in principle, but there is always the possibility of interference due to unexpected substances in the samples that have the identical mass transitions as the target analytes (isomeric/isobaric interferences). By recording the ion ratio (IR), clinical laboratories already widely attempt to identify such interferences in individual cases. To supplement this procedure, differential tuning effects can be assessed. We aimed to evaluate this approach experimentally. Methods: The detuning ratio (DR) is based on the differential influences of MS instrument settings on the ion yield of a respective target analyte; isomeric or isobaric interferences can lead to a shift of the DR for an affected sample. By determining the DR in samples in which known isomeric interference substances have been spiked to the target analyte, the applicability of DR detection was quantitatively investigated. Results: It was observed in two independent exemplary test systems (Cortisone / Prednisolone and O-Desmethylvenlafaxine / cis-Tramadol HCl) that a DR can indicate the presence of isomeric interferences. Conclusion: It was confirmed that a DR can be used as a method to obtain indications of the presence of isomeric or isobaric interferences in individual samples in an analytical LC-MS/MS system; the technique can be used in addition to the established method of IR detection to increase the analytical reliability of clinical MS analyses.Abbreviations: CE, collision energy; CID, collision induced dissociation; CXP, cell exit potential; CLSI, Clinical and Laboratory Standards Institute; DR, detuning ratio; ESI+, positive electrospray ionization; IR, ion ratio; IS, internal standard; LC, liquid chromatographic; LC-MS/MS, liquid chromatography tandem mass spectrometry; ME, matrix effects; MRM, multiple reaction monitoring; MS, mass spectrometry; m/z, mass-to-charge ratio; TIC, Total ion current.